2019 Global Medical Engineering Physics Exchanges/ Pan American Health Care Exchanges (GMEPE/PAHCE) 2019
DOI: 10.1109/gmepe-pahce.2019.8717362
|View full text |Cite
|
Sign up to set email alerts
|

Spatio Temporal Parameters and Symmetry Index in Transtibial Amputees Wearing Prosthetic Feet with and without Adaptive Ankles

Abstract: This study measured spatio temporal parameters (STP) and their symmetry index (SI) in order to evaluate the differential effect on the gait pattern of individuals with unilateral transtibial amputations when using two different prostheses. Twelve individuals with transtibial amputations walked on level ground using an Energy Storage and Return (ESAR) prosthesis with fixed ankle and a prosthetic foot with adaptive ankle (PFAA). The STP were measured in the prosthetic and sound limbs and the symmetry index for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Other studies measured spatio temporal parameters in amputees walking on level ground and reached similar results [21], [30], [31]. In particular, Kovac et al [30] studied differences in STP between healthy and transtibial amputees with their current prosthetic foot.…”
Section: Spatio Temporal Parameters (Stp)mentioning
confidence: 61%
See 2 more Smart Citations
“…Other studies measured spatio temporal parameters in amputees walking on level ground and reached similar results [21], [30], [31]. In particular, Kovac et al [30] studied differences in STP between healthy and transtibial amputees with their current prosthetic foot.…”
Section: Spatio Temporal Parameters (Stp)mentioning
confidence: 61%
“…Similar results have been reported in the literature. For example, symmetry values greater than 88% have been reported in UTTA [17], [21], [32], [33], while results greater than 94% were found for unimpaired subjects [33], [34].…”
Section: Symmetry Index (Si)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that wearing active prostheses can make the gait of disabled people more comfortable 2,3 . It also increases their ability to walk steadily on various terrains 4,5 . Most common transfemoral prostheses only have knee and ankle joints, while toe joint is usually ignored, and the feet are all single‐structure carbon fibre feet 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Advanced gait analysis systems can provide objective and quantitative kinematics and kinetics data. Typically, these more involved gait analyses involve comparison to some gold standard, either a set of control data that represents good gait(2), or there is an assumption made that bilateral symmetry represents good gait (3)(4)(5). Currently, there is not good agreement in the literature about how to best assess gait quality.…”
mentioning
confidence: 99%